Postoperative functional outcomes in patients with highly migrated cervical disc prolapse - Periyasamy, Mohan; Gandham, Edmond Jonathan; Joseph, Jeena; Raju, Krishna Prabhu (Nepal Journal of Neuroscience, 2025)
Introduction: Cervical spondylotic myelopathy resulting from a highly migratory disc prolapse is an infrequent occurrence, typically associated with patients presenting with poor Nurick grades. The debate around the choice of therapy between discectomy versus corpectomy is a topic of contention. In this study, we describe our findings on the utilization of corpectomy as the preferred therapeutic approach. Methods: In this retrospective study a cohort of 12 patients were included during the study period. The variables studied encompassed demographic aspects, clinical presentation, radiological data, as well as the rates of recovery for both Nurick and mJOA (Modified Japanese orthopedic association) scales. Results: The average age at presentation was 52.8 years, with a range of 42 to 64 years. The male-to-female ratio was 1:1. At presentation, the mean Nurick grade was four and the mean mJOA score was 9.8. The average duration of the symptoms was 17 months. The median follow-up period was 25 months (range:12-72 months). Based on pre operative MRI scans, the migration distance of disc prolapses ranged from 6.5-18.8 mm with mean of 9.9 mm. At follow-up, the mean Nurick grade recovery rate was 49.58 + 22.74 % and the mean mJOA recovery rate was 58.42 + 24.77% (p=0.04). There were no complications. Conclusion: Based on our empirical observations, corpectomy appears to be an optimal surgical approach for patients presenting with highly migrated disc prolapse. This procedure offers a broader surgical field, facilitating the removal of fragments located posterior to the vertebral body and those that are adherent to the thecal sac.